2019
DOI: 10.3390/foods8090357
|View full text |Cite
|
Sign up to set email alerts
|

Producing an Emulsified Meat System by Partially Substituting Pig Fat with Nanoemulsions that Contain Antioxidant Compounds: The Effect on Oxidative Stability, Nutritional Contribution, and Texture Profile

Abstract: The objective of this study was the incorporation of a water–oil (W/O) nanoemulsion for the partial substitution of pig fats and the addition of antioxidant compounds in an emulsified meat system (EMS). The nanoemulsion was formulated with orange essential oil and cactus acid fruit (xoconostle). The treatments were different percentages (0, 1, 2, 3, 4, and 5%) of the nanoemulsion for the substitution of pig fat in the EMS. The proximal analysis (moisture, protein, fat, and ash), texture profile (hardness, cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…The increase in fat may be due to the composition of the nanoemulsion, which contains orange essential oil, causing a similar effect as reported by Almaráz-Buendia et al [ 22 ]. They added nanoemulsion containing orange essential oil in sausages and observed a directly proportional increase in their fat content, since this oil is mainly comprised of terpenes.…”
Section: Discussionsupporting
confidence: 71%
“…The increase in fat may be due to the composition of the nanoemulsion, which contains orange essential oil, causing a similar effect as reported by Almaráz-Buendia et al [ 22 ]. They added nanoemulsion containing orange essential oil in sausages and observed a directly proportional increase in their fat content, since this oil is mainly comprised of terpenes.…”
Section: Discussionsupporting
confidence: 71%
“…The increase in ash is due to the incorporation of whey protein, which there is evidence showing that it contains a good concentration in its composition (Morr & Ha, 1993). A similar effect was observed by Almaráz‐Buendia et al (2019) when he substituted animal fat with nanoemulsion of bioactive compounds of orange and xoconostle in meat products.…”
Section: Resultssupporting
confidence: 79%
“…Physicochemical analyses of the different meat products were carried out according to the method reported by Almaráz‐Buendia et al (2019). Moisture was determined by weight difference after drying the samples at 100℃ for 8 hr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, encapsulation of these essential oils in well‐designed nanoemulsions can enhance their stability, ease of utilization, and efficacy (Moradi & Barati, 2019; Rao et al., 2019). Various researchers have reported that essential oil encapsulated within nanoemulsions have strong antimicrobial and/or antioxidant activity, including cinnamon and thyme oils in beef patties (Ghaderi‐Ghahfarokhi, Barzegar, Sahari, & Azizi, 2016), ginger oil in chicken breast fillets (Noori, Zeynali, & Almasi, 2018), citrus oil in fresh silvery pomfret ( Pampus argenteus ) fillets (Wu et al., 2016), orange oil in emulsified meats (Almaráz‐Buendia et al., 2019), anise oil in Yao meat products (Liu, Zhang, Bhandari, Xu, & Yang, 2020), oregano oil for fresh pork loins (Xiong et al., 2020), Ferulago angulata oil (Shokri, Parastouei, Taghdir, & Abbaszadeh, 2020) and garlic oil in beef meat sausages (Esmaeili et al., 2020). Some nutraceuticals loaded into nanoemulsions have also been shown to exhibit antimicrobial activity, such as curcumin in chicken fillets (Abdou et al., 2018; Khan, Sadiq, & Mehmood, 2020).…”
Section: Nanoemulsion‐based Delivery Systems For Muscle Food Applicatmentioning
confidence: 99%